Control of Varroa destructor development in Africanized Apis mellifera honeybees using Aluen Cap (oxalic acid formulation) - Rodríguez Dehaibes, Sóstenes Rafael (2020)
Aluen Cap is an oxalic acid (OA) formulation that shows promise as a control method for Varroa destructor. This work explores the use and efficacy of Aluen Cap against V. destructor in Africanized honeybees in Veracruz Mexico, where capped brood is always present across the year and acaricide resistance was a problem. Twenty-four beehives were assessed over 42 days, a period of time associated with the liberation of OA from Aluen Cap. The acaricide formulation shows significantly higher mean efficacy (92.1%) than control hives (36.5%). This test suggests the high value of the new oxalic acid formulation in AHBs despite the high temperatures and presence of brood, avoiding the necessity of multiple applications of OA, hence simplifying colony management.